A simple method to interpret the rheological behaviour of intercalated polymer nanocomposites. (1st August 2016) - La Mantia, F.P.; Scaffaro, R.; Ceraulo, M.; Mistretta, M.C.; Dintcheva, N.Tz.; Botta, L.
Abstract: Nanocomposites are a new class of polymer composites that exhibit an interesting combination of chemical, physical, thermal and mechanical properties. Only small amounts of nanofiller are sufficient to generate great variations of many properties. This work focuses on the rheological behaviour of the intercalated polymer nanocomposites in shear flow. The increase of the viscosity and the more pronounced non-Newtonian behaviour is interpreted simply considering the increase of volume of the inert phase caused by the intercalation of the macromolecules. Indeed, the volume of the intercalated tactoids increases with increasing the interlayer distance. On the other hand, the interlayer distance can be correlated with the increase of the viscosity or with the more pronounced non-Newtonian behaviour. This simple method cannot be applied to exfoliated nanocomposites or when interactions between the matrix and the nanoclay occur, thus leading to a modification of the polymer chains, e.g., degradation of the matrix due to the interaction with the organo-modifier of the clay.